EMOTIONAL INTELLIGENCE : PENGARUH TERHADAP KEPEMIMPINAN TRANSFORMATIONAL DAN KOHESIVITAS KELOMPOK (Studi empiris KSOP Kelas I Pelabuhan Indonesia) - Honorata Ratnawati Dwi Putranti; Mohammad Faisal Burhan (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
The purpose of this study is to test the new hypothesis about the direct and indirect effects of Emotional Intelligence on group cohesiveness. public organizations are still not fully able to create a good service system in the eyes of the people. Such conditions certainly require leaders who can be visionary and collaborate well between parts for a change. The population in this study were all (employees) with a minimum of 4 (four) echelon positions in 9 1st class KSOP(Kesyahbandaran dan Otoritas Pelabuhan) locations in Indonesia. The sample technique in this study was carried out by stratified random sampling technique, namely samples taken with special conditions. The sample used in each location is 9 people and the financial part is 8 people. The results of the study are the results of the path analysis test showing that emotional intelligence influences group cohesiveness through transformational leadership as mediation. This shows that an increase in emotional intelligence will make the implementation of transformational leadership better.